2020
DOI: 10.1111/petr.13818
|View full text |Cite
|
Sign up to set email alerts
|

Anemia after kidney transplantation: Does its basis differ from anemia in chronic kidney disease?

Abstract: Background: Although similar factors play a role in both PTA and anemia in patients with CKD, additional risk factors exist in the pathogenesis of PTA. The present study aimed at comparing anemia and inflammation-related parameters between RTx recipients and CKD patients and elucidating the risk factors of PTA. Methods: This single-centered, cross-sectional study consisted of 68 participants: 48 were in the RTx group and 20 were in the CKD group. The CKD patients were comparable to the RTx recipients in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a study of 147 pediatric patients, White et al found higher odds of developing anemia at all stages of CKD in transplant recipients vs. patients with native CKD ( 5 ). Similarly a recent pediatric study by Oruc et al showed lower hemoglobin ( p = 0.04) despite a higher erythropoietin level ( p < 0.001) in transplant recipients compared with GFR-matched native CKD patients ( 35 ). These data suggest that additional mechanisms are at play in the posttransplant population.…”
Section: Anemia Of Chronic Kidney Diseasementioning
confidence: 69%
See 1 more Smart Citation
“…In a study of 147 pediatric patients, White et al found higher odds of developing anemia at all stages of CKD in transplant recipients vs. patients with native CKD ( 5 ). Similarly a recent pediatric study by Oruc et al showed lower hemoglobin ( p = 0.04) despite a higher erythropoietin level ( p < 0.001) in transplant recipients compared with GFR-matched native CKD patients ( 35 ). These data suggest that additional mechanisms are at play in the posttransplant population.…”
Section: Anemia Of Chronic Kidney Diseasementioning
confidence: 69%
“…A cross-sectional study of 45 pediatric kidney transplant recipients found a 62% prevalence of CKD stage 3 or higher ( 5 ). Although graft dysfunction is a significant cause of PTA, adult and pediatric data indicate a higher prevalence and greater severity of PTA compared with native CKD for the same level of kidney dysfunction ( 5 , 35 , 36 ). In a study of 147 pediatric patients, White et al found higher odds of developing anemia at all stages of CKD in transplant recipients vs. patients with native CKD ( 5 ).…”
Section: Anemia Of Chronic Kidney Diseasementioning
confidence: 99%
“…For renal transplantation patients, delayed graft function, allograft rejection, and calcineurin inhibitor toxicity all can induce renal tubular injury, which then leads to decreased EPO secretion in tubules. 43 Treatment with roxadustat can help to relieve inflammation and renal tubular injury, 44 which may be one of the potential mechanisms underlying the effectiveness of roxadustat in treating PTA.…”
Section: Discussionmentioning
confidence: 99%